Forensic Tools Performance Analysis on Android-based Blackberry Messenger using NIST Measurements - Imam Riadi; Rusydi Umar; Arizona Firdonsyah (Institute of Advanced Engineering and Science, 2018)
Blackberry Messenger is one of the popularly used instant messaging applications on Android with user’s amount that increase significantly each year. The increase off Blackberry Messenger users might lead to application misuse, such as for commiting digital crimes. To conduct investigation involving smartphone devices, the investigators need to use forensic tools. Therefore, a research on current forensic tool’s performance in order to handle digital crime cases involving Android smartphones and Blackberry Messenger in particular need to be done. This research focuses on evaluating and comparing three forensic tools to obtain digital evidence from Blackberry Messenger on Android smartphones using parameter from National Institute of Standard Technology and Blackberry Messenger’s acquired digital evidences. The result shows that from comparative analysis conducted, Andriller gives 25% performance value, Oxygen Forensic Suite gives 100% performance value, and Autopsy 4.1.1 gives 0% performance value. Related to National Institute of Standard Technology parameter criterias, Andriller has performance value of 47.61%. Oxygen Forensic Suite has performance value of 61.90%. Autopsy 4.1.1 has performance value of 9.52%.